Construction of a Z-DNA-specific restriction endonuclease - Kim, Yang-Gyun (The National Academy of Sciences of the USA, 1997)
Novel restriction enzymes can be created by fusing the nuclease domain of FokI endonuclease with defined DNA binding domains. Recently, we have characterized a domain (Zα) from the N-terminal region of human double-stranded RNA adenosine deaminase (hADAR1), which binds the Z-conformation with high specificity. Here we report creation of a conformation-specific endonuclease, Zα nuclease, which is a chimera of Zα and FokI nuclease. Purified Zα nuclease cleaves negatively supercoiled plasmids only when they contain a Z-DNA forming insert, such as (dC-dG)(13). The precise location of the cleavage sites was determined by primer extension. Cutting has been mapped to the edge of the B-Z junction, suggesting that Zα nuclease binds within the Z-DNA insert, but cleaves in the nearby B-DNA, by using a mechanism similar to type IIs restriction enzymes. These data show that Zα binds Z-DNA in an environment similar to that in a cell. Zα nuclease, a structure-specific restriction enzyme, may be a useful tool for further study of the biological role of Z-DNA.